2009
DOI: 10.1243/03093247jsa515
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of effective stress intensity factors using thermoelastic stress analysis

Abstract: It has been demonstrated that thermoelastic stress analysis (TSA) can provide accurate information about the real crack-driving force for fatigue crack growth. Experiments were conducted using aluminium 2024 compact tension specimens which were initially precracked to different crack lengths at a constant R (R 5 0). Subsequently, thermoelastic images were captured at increasing R values from 0 to 0.5 and DK values from 3 to 6 MPa m 0.5 were calculated. The images showed a dramatic change in the stress pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Studies have also been done to examine the influence of crack closure and residual stress on the thermoelastic response of a crack. The effects are noticeable 25 and support conclusions that the SIF deduced from TSA is the effective value (DK eff ), 30 which reflects the actual rather than nominal driving force for crack growth. The distinction was illustrated in Diaz et al, 26 where SIF measurements furnished by TSA matched theoretical values only once the latter were corrected for the influence of closure and residual stress.…”
Section: Rajic and Stevesupporting
confidence: 64%
“…Studies have also been done to examine the influence of crack closure and residual stress on the thermoelastic response of a crack. The effects are noticeable 25 and support conclusions that the SIF deduced from TSA is the effective value (DK eff ), 30 which reflects the actual rather than nominal driving force for crack growth. The distinction was illustrated in Diaz et al, 26 where SIF measurements furnished by TSA matched theoretical values only once the latter were corrected for the influence of closure and residual stress.…”
Section: Rajic and Stevesupporting
confidence: 64%
“…Previous studies 42,45 have shown that frictional heating of the crack flanks is readily detectable by TSA and it is apparent in Fig. 5c, e, g and h as very small bright horizontal lines extending radially, to the left, from the hole.…”
Section: Resultsmentioning
confidence: 53%
“…Indeed, the literature is full of examples of highly successful practical applications (e.g. [10][11][12]). …”
Section: Thermoelasticitymentioning
confidence: 99%